The Ambidextrous Role of Inland Terminals in Enhancing Port–Hinterland Connectivity - Tomislav Rožić; Diana Božić; Ivona Bajor; Berislav Andrlić (Logistics)
Background: The operational roles of ports are deeply intertwined with the development of their surrounding hinterlands, indicating that their relationship is mutually dependent and interactive. Moreover, the growth of a port positively influences the development of its hinterland, stimulating economic activities and improving overall regional development by enhancing competitiveness. Inland terminals, often considered “extended gateways” to ports, play a crucial role in integrating ports with their hinterlands. These terminals facilitate the adjustment of cargo transportation to align with the operational dynamics of ports. This paper presents a framework designed to clarify the importance of fostering strong links between ports and their hinterlands through the establishment of inland terminals. Methods: By applying a conceptual framework and methodologies of literature review and content analysis, this paper highlights the critical importance of developing robust connections between ports and their hinterlands through the implementation of inland terminals. Results and Conclusions: The findings of this research can help map the scientific knowledge related to various metrics of port–hinterland connectivity, outline relevant thematic areas, visualize the relationships between ports and their hinterlands, and identify prevailing research gaps and potential research paths in the context of inland terminal integration into the port system.